Revitalizing the Adamawa Economy Post-COVID-19: An Islamic Economic Approach - Yakubu, Aminu; Abubakar, Salihu Muhammad; Badamasi, Nuru; Fadimatu A. Jika (International Journal of Religious and Interdisciplinary Studies, 2024)
The COVID-19 pandemic has severely impacted the global economy, with developing countries like Nigeria being particularly vulnerable. Within Nigeria, Adamawa State stands out as one of the regions most affected by the socio-economic consequences of the pandemic. This study seeks to investigate the potential of the Islamic economic system as a viable solution to the economic challenges faced by Adamawa in the post-pandemic era. By employing a qualitative research approach, the study gathered data through structured interviews with Islamic economists and members of the general public. The findings indicate that Islamic financial instruments—such as zakat, waqf, and sadaqah—possess significant potential to facilitate a more inclusive and sustainable economic recovery. These instruments could be vital in addressing inequality and providing a safety net for vulnerable communities. Moreover, the framework proposed in the study highlights how these financial tools can generate employment opportunities and enhance social welfare. The study offers valuable insights into the practical application of Islamic economic principles as part of the region's recovery strategy. Furthermore, it recommends future research to explore the implementation of these financial instruments at the local level, ensuring that the proposed solutions align with the unique socio-economic landscape of Adamawa State.